Factors Affecting The Quality Of Life Of Elderly In The Working Area Of Anggut Atas Health Center, Bengkulu City In 2024 - Moneca, Elsa; Handayani, Tita Septi; Tranado, Hengki (Journal of Multidisciplinary Research, 2025)
The quality of life and life expectancy are important for the elderly. A good quality of life for the elderly will encourage them to be healthier, more independent, productive, and prosperous. Quality of life is used as an important indicator to assess health service interventions in terms of both prevention and treatment. Many factors can affect the quality of life of the elderly. The objective of this study is to identify the factors affecting the quality of life of elderly in the Working Area of Anggut Atas Health Center, Bengkulu City in 2024. The research method used in this study is quantitative research using a cross-sectional design. The sample size used in this study is 93 individuals, with the sampling technique employed being propositional sampling. Based on the research results, it was found that the majority of respondents had supportive family support, more than half of the respondents had negative peer support, the majority of respondents were married, and more than half of the respondents had good quality of life. There is a relationship between family support (p-value = 0.007), peer support (p-value = 0.018), marital status (p-value = 0.002), and the quality of life of elderly in the Working Area of Anggut Atas Health Center, Bengkulu City. The researcher recommends that healthcare workers maintain and improve the quality of life of elderly by providing education and counseling to the elderly in conducting routine check-up programs at Posyandu.